Autobiographical memory deficits in patients with depression follow a temporal distribution - Biedermann, Sarah Violetta; Sartorius, Alexander; Ende, Gabriele (Psychiatry research, 2017)
Autobiographical memory deficits are known in depression. The temporal distribution thereof across periods of life has rarely been considered yet. Autobiographical memories for 5 life periods were investigated in 27 depressed in-patients and compared to 31 matched healthy controls using the Bielefelder Autobiographisches Gedächtnis Inventar. Depressed patients reported significantly less details in memories dating from childhood to 30 years, correlating with severity of depression. Memories from childhood and recent periods were less positive in depressed patients. Thus, we found a distinct pattern of autobiographical memory deficits in depressed patients. Possible etiological factors, however, need further investigations.
Available online26 July 2017
Gesehen am 13.06.2018